Understanding symptoms in the lives of adult patients with acute or chronic illness: a phenomenological study of patient experiences - Malene Missel; Linda Kahr Andersen; Camilla Corvinius; Maria Camilla Mathiasen; Pernille Orloff Donsel; Mai Nanna Schønau; Helle Pappot; Nanna Witting; Melissa Culligan; Giulia Locatelli; Mary Jarden; Karin Piil (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Exploring how patients with acute and/or chronic illnesses experience symptoms. Methods Using a phenomenological approach, interviews were conducted with patients to gain insights into their lived experiences and the meanings they attribute to symptoms. Phenomenological concepts of lifeworld, body and embodiment, intentionality, and existential anxiety provide lenses for examining the realities of patients’ experiences. Results Three central themes emerged from the Ricoeur inspired analysis: Perception of an altered body presence, which highlights how illness transforms the perception of the body from a “silent” part of the self to an intrusive presence; Symptoms as a threat to existence, illuminating how symptoms confront patients with vulnerability, mortality, and existential uncertainty; and Loss and reclaiming of control, describing the ongoing struggle patients face between feelings of helplessness and efforts to regain autonomy in daily life.Symptoms are not merely indicators of illness but are intertwined with patients’ identities and their sense of meaning in life. Conclusion Insights emphasize the importance of addressing both the biological and existential dimensions of symptoms. Face-to-face clinical encounters offer a shared opportunity to create reflective spacesValidating coping strategies and supporting patients in reclaiming control, clinicians can nurture resilience, dignity, and a comprehensive approach to symptom (self)management.